Awareness on Mental Illness among Adults of a Community in Ilam - Giri, S.; Chhetri, P.K.; Sherpa, P.G. (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Background: Mental illness is an increasing public health problem globally, especially in developing countries which affects overall quality of life. It is a neglected area of health which is highly stigmatized. The objective of the study was to find out awareness on mental illness among community people of Ilam District. Method: A descriptive cross sectional study was conducted among 80 respondents of Ilam District using non-probability purposive sampling technique. Face to face interview technique was used to collect data by using self- developed structured questionnaire. Data management, analysis and interpretation as done using descriptive and inferential statistics in SPSS and represented in tabulated form. Result: The findings of the study showed that (61.2 %) of the respondents had adequate level of awareness. Adequate level of awareness was present on meaning (71.2%), common type of mental illness in adults (77.50%), treatment (76.2%) and continue medicine and timely follow up are relapse prevention (96.2%). However inadequate awareness was present on brain injury as a biological risk factors (20.0%), Seeing/hearing things that no one else can see or hear (7.5%) and violent behavior (10%) as sign symptoms and impairment of family relation as complications (31.3.%). Conclusion: The study revealed that more than 3/5 of the respondents had adequate level of awareness on mental illness.